Association Between Pulmonary Embolism and COVID‐19 in Emergency Department Patients Undergoing Computed Tomography Pulmonary Angiogram: The PEPCOV International Retrospective Study. (4th September 2020) - Freund, Yonathan; Drogrey, Marie; Miró, Òscar; Marra, Alessio; Féral‐Pierssens, Anne‐Laure; Penaloza, Andrea; Hernandez, Barbara A. Lara; Beaune, Sebastien; Gorlicki, Judith; Vaittinada Ayar, Prabakar; Truchot, Jennifer; Pena, Barbara; et al.
Abstract: Background: There have been reports of procoagulant activity in patients with COVID‐19. Whether there is an association between pulmonary embolism (PE) and COVID‐19 in the emergency department (ED) is unknown. The aim of this study was to assess whether COVID‐19 is associated with PE in ED patients who underwent a computed tomographic pulmonary angiogram (CTPA). Methods: A retrospective study in 26 EDs from six countries. ED patients in whom a CTPA was performed for suspected PE during a 2‐month period covering the pandemic peak. The primary endpoint was the occurrence of a PE on CTPA. COVID‐19 was diagnosed in the ED either on CT or reverse transcriptase–polymerase chain reaction. A multivariable binary logistic regression was built to adjust with other variables known to be associated with PE. A sensitivity analysis was performed in patients included during the pandemic period. Results: A total of 3, 358 patients were included, of whom 105 were excluded because COVID‐19 status was unknown, leaving 3, 253 for analysis. Among them, 974 (30%) were diagnosed with COVID‐19. Mean (±SD) age was 61 (±19) years and 52% were women. A PE was diagnosed on CTPA in 500 patients (15%). The risk of PE was similar between COVID‐19 patients and others (15% in both groups). In the multivariable binary logistic regression model, COVID‐19 was not associated with higher risk of PE (adjusted odds ratio = 0.98, 95% confidence interval = 0.76 to 1.26). There was no association when limited to patients in the pandemic period. Conclusion: In ED patients who underwent CTPA for suspected PE, COVID‐19 was not associated with an increased probability of PE diagnosis. These results were also valid when limited to the pandemic period. However, these results may not apply to patients with suspected COVID‐19 in general.